Coordination, organizations, institutions, and norms in agent systems XII : COIN 2016 International Workshops, COIN@AAMAS, Singapore, Singapore, May 9, 2016, COIN@ECAI, the Hague, the Netherlands, August 30, 2016, Revised selected papers /: COIN 2016 International Workshops, COIN@AAMAS, Singapore, Singapore, May 9, 2016, COIN@ECAI, the Hague, the Netherlands, August 30, 2016, Revised selected papers. (2017) - Unknown
No abstract available